2011 IEEE International Interconnect Technology Conference 2011
DOI: 10.1109/iitc.2011.5940307
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental study of atomic layer deposition in and on porous low-k films

Abstract: Atomic layer deposition is a promising technique to deposit conformal, nm-thin metal barriers in high aspect ratio trenches. However, exactly because of its excellent conformality, the deposition can also occur inside the nanopores of the most advanced low-k materials. In this work, the mechanisms of atomic layer deposition on and in low-k, porous dielectric films were studied, using HfO 2 as a test material. Exhaustive analyses showed firstly that the HfCl 4 precursor penetrated uniformly in the pores through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Because the dielectric constant is highly sensitive to physical and chemical damage, a sealing layer is required to shield the pores from moisture, gas precursors, and plasma radicals that are involved in subsequent processing steps. Some authors have investigated the use of ALD to seal the pores of low- k dielectrics. …”
Section: Introductionmentioning
confidence: 99%
“…Because the dielectric constant is highly sensitive to physical and chemical damage, a sealing layer is required to shield the pores from moisture, gas precursors, and plasma radicals that are involved in subsequent processing steps. Some authors have investigated the use of ALD to seal the pores of low- k dielectrics. …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that for example gas permeance strongly depends on pore size and that the selectivity between He, N 2 , and SF 6 increases logarithmically as the pore size decreases (16). For the deposition of HfO 2 on porous low-k using HfCl 4 and H 2 O, it was shown that when the pore sized decreased as a result of the deposition, the porous material became first inaccessible for the larger HfCl 4 molecules, and only at a later stage for the smaller H 2 O molecules (17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the decrease in mechanical strength of the porous ultralow- k (ULK) dielectrics may cause a premature package failure during chip-package interactions . Penetration of Cu and barrier metal precursors deep into the porous dielectrics is also a serious issue, which would hamper the precise control of critical dimensions (CDs) and the formation of continuous barriers, resulting in reliability degradation in ICs. , Recently, therefore, pore sealing of the porous ULK dielectrics has been intensively studied. While many types of methods have been proposed for this purpose, the drawbacks of each suggested method, such as an excessive increase of the dielectric thickness, , dielectric damage by plasmas, a conformality issue, and difficulty in scalability, have limited their practical application to mass production.…”
mentioning
confidence: 99%